The Fermat–Steiner Problem in the Space of Compact Subsets of the Euclidean Plane - Galstyan, A. H. (Journal of mathematical sciences (New York, N.Y.), 2023)
The Fermat–Steiner problem is the problem of finding all points of a metric space Y such that the sum of the distances from them to points of a certain fixed finite subset A of the space Y is minimal. In this paper, we examine the Fermat–Steiner problem in the case where Y is the space of compact subsets of the Euclidean plane endowed with the Hausdorff metric, and points of A are finite pairwise disjoint compact sets.